2009
DOI: 10.1002/jts.20422
|View full text |Cite
|
Sign up to set email alerts
|

Male‐to‐female sexual aggression among Iraq, Afghanistan, and Vietnam veterans: Co‐occurring substance abuse and intimate partner aggression

Abstract: The current study examined the frequency and correlates of coercive sexual behaviors by male Iraq, Afghanistan, and/or Vietnam veterans recruited from a Veterans Affairs trauma recovery clinic (n = 92) toward their female partners. Men who reported sexual aggression in the past year (n = 37) compared to men who did not report sexual aggression in the past year (n = 55) more frequently reported impulsive aggression, dominating/isolating, and physically assaulting their partner, and were more likely to have a su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(46 citation statements)
references
References 21 publications
1
45
0
Order By: Relevance
“…The excluded studies included ten which questioned only the service person themselves (Fonseca et al ., 2006;Gerwitz et al ., 2010;McLeland et al ., 2008;Meis et al ., 2010aMeis et al ., , 2010bRenshaw et al ., 2009;Sayers et al ., 2009;Teten et al ., 2009Teten et al ., , 2010Forgey & Badger, 2006) and two qualitative studies (Lapp et al ., 2010;Goff et al ., 2006).…”
Section: Inclusion Criteriamentioning
confidence: 94%
“…The excluded studies included ten which questioned only the service person themselves (Fonseca et al ., 2006;Gerwitz et al ., 2010;McLeland et al ., 2008;Meis et al ., 2010aMeis et al ., , 2010bRenshaw et al ., 2009;Sayers et al ., 2009;Teten et al ., 2009Teten et al ., , 2010Forgey & Badger, 2006) and two qualitative studies (Lapp et al ., 2010;Goff et al ., 2006).…”
Section: Inclusion Criteriamentioning
confidence: 94%
“…One study of N =101 Veterans found that 67% of younger men (age ≤ 40 years) reported physically hurting the woman they lived with compared to 43% of older men (age >40) χ 2 (l, 101) = 5.68, p < .02 (Petrik et al, 1983). With respect to personality traits, Veterans who scored higher on measures of dominance and isolation were more likely to be sexually, rather than non-sexually, aggressive (Teten, Schumacher, Bailey, & Kent, 2009). Group-level attitudes during military service may be predictors of intimate partner violence and include lower perception of support from leaders and chain of command, a culture of hypermasculinity (i.e., having degrading conversation about women with fellow troops), and lower recognition of and provision for needs of spouses (Rosen, Kaminski, Parmley, Knudson, & Fancher, 2003).…”
Section: Findings From Review Of Risk Factors For Intimate Partner/domentioning
confidence: 99%
“…Further, more severe PTSD symptoms are related to a higher frequency of violent behavior (Orcutt et al, 2003). With regard to specific types of violence, PTSD diagnoses did not differ for sexually aggressive versus nonsexually aggressive Veterans (Teten, Schumacher, Bailey, & Kent, 2009) but were more prevalent among Veterans in mutually violent couples (Teten, Sherman, & Han, 2009). …”
Section: Findings From Review Of Risk Factors For Intimate Partner/domentioning
confidence: 99%
See 1 more Smart Citation
“…This broad definition of dominance is important since many studies on a possible relationship between dominance and sexual aggression have focused on more specific aspects of dominance. For example, some studies emphasized the motive to have sex in order to feel powerful or in control (Brousseau, Hebert, & Bergeron, 2012;Wheeler, George, & Dahl, 2002) while others investigated direct dominance over the female partner in the sense of isolating the woman from social resources and the demand for subservience (Gage, 2005;Teten, Schumacher, Bailey, & Kent, 2009). These more specific, often sex-related, concepts of dominance might be seen as parts of hostile masculinity rather than general dominance in the sense of instrumentality (Abbey, Parkhill, BeShears, Clinton-Sherrod, & Zawacki, 2006).…”
Section: Introductionmentioning
confidence: 99%